Pemberdayaan Perempuan Dalam Meningkatkan Pendapatan Keluarga Melalui Kelompok Tenun Mawar Di Desa Tanah Merah, Kecamatan Kupang Tengah, Kabupaten Kupang - Seran, Apriliana Hoar; Simbolon, Gallex; Mardani, Ambara Saraswati (Universitas Nusa Cendana, 2025)
The women's empowerment program in the family environment is one of the strategic steps in improving household welfare, along with economic demands, women now have an important role in supporting the resilience of family life. This encourages the involvement of women working in productive activities such as women's empowerment programs through weaving groups as part of village development and brings change for women in changing family lives. This study aims to examine how the role of the rose weaving group in increasing women's household income in Tanah Merah Village. The research approach used is a qualitative method with Longwe Analysis, this study examines 5 dimensions of empowerment, namely (1) Welfare dimension (2) Access dimension (3) Critical awareness dimension (4) Participation dimension (5) Control dimension. The results of the study show that the involvement of women members of the weaving group has a positive impact on family income. Because through the women's weaving group they are able to generate additional income that can help meet the needs in the household and are not dependent on their husbands.